2019
DOI: 10.2460/ajvr.80.6.558
|View full text |Cite
|
Sign up to set email alerts
|

Radiation exposure of dogs and cats undergoing fluoroscopic procedures and for operators performing those procedures

Abstract: OBJECTIVE To evaluate radiation exposure of dogs and cats undergoing procedures requiring intraoperative fluoroscopy and for operators performing those procedures. SAMPLE 360 fluoroscopic procedures performed at 2 academic institutions between 2012 and 2015. PROCEDURES Fluoroscopic procedures were classified as vascular, urinary, respiratory, cardiac, gastrointestinal, and orthopedic. Fluoroscopy operators were classified as interventional radiology-trained clinicians, orthopedic surgeons, soft tissue surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Fluoroscopy unit dose for the 37 orthopedic cases, of which three were SIL, was reported to yielded a mean of 2.27 mGy (range, 0.14–74.33), which is similar but has a much wider range compared with the present study of 17 SIL cases with a mean of 2.36 ± 1.39 mGy (range, 0.38–4.7). The previous report 21 described median fluoroscopic screening time (1.71 minutes), while, in the present study, we used only still shot mode and reported a mean of 37.63 shots, which makes comparing these results difficult. Over the course of 17 cases and 639 acquired images, only the assistant had detectable exposure on the wrist of their dominant arm, with a cumulative dose of 0.4 mrem.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Fluoroscopy unit dose for the 37 orthopedic cases, of which three were SIL, was reported to yielded a mean of 2.27 mGy (range, 0.14–74.33), which is similar but has a much wider range compared with the present study of 17 SIL cases with a mean of 2.36 ± 1.39 mGy (range, 0.38–4.7). The previous report 21 described median fluoroscopic screening time (1.71 minutes), while, in the present study, we used only still shot mode and reported a mean of 37.63 shots, which makes comparing these results difficult. Over the course of 17 cases and 639 acquired images, only the assistant had detectable exposure on the wrist of their dominant arm, with a cumulative dose of 0.4 mrem.…”
Section: Discussionmentioning
confidence: 68%
“…The six cases that did not require reduction required acquisition of fewer fluoroscopic images and took less time to complete, thus skewing the results of this study. Fluoroscopic use was limited to still shots rather than cine mode, as has been described in other reports 21,26 . Use of cine mode may have decreased cadaver positioning and surgical durations, but at the cost of increased radiation exposure.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…While several of the above studies state that estimated annual doses will be well below regulatory limits for a given caseload, other studies of occupational doses in veterinary medicine have found that personnel doses may approach annual dose limits recommended by ICRP (Table 4.1) (Hernández-Ruiz et al., 2012; Canato et al., 2014). (128) Recently, dosimetric data have been published for veterinary interventional radiology and intra-operative fluoroscopically guided surgery, where there is close proximity between personnel and animal patients during exposure, often for extended periods (Sung et al., 2018; An et al., 2019; Hersh-Boyle et al., 2019). Reported operator dose levels may approach or even exceed regulatory limits, which emphasises the need for both quantitative radiation monitoring and the use of appropriate protective measures during these procedures. (129) With regards to dose to the animal patient, few dosimetric studies have been published.…”
Section: Application Of the System Of Radiological Protection To Vete...mentioning
confidence: 99%